Recurrent relations for the solutions of an infinite system of linear algebraic equations
We obtain recurrent relations for bounded solutions of the system of equations X_k - _n = 0^∞ (k + n)! k!n! α ^k + n + 1 x_n = f_k, k = 0,1,..., α (0,1/2), with right-hand sides f k k=0 ∞ =δ kj k=0 ∞